KONDISI FAKTUAL DAN FAKTOR-FAKTOR PENENTU PEMENUHAN PENDIDIKAN DASAR DAN MENENGAH DI KAWASAN PERBATASAN - Endah Rantau Itasari (Jurnal Komunikasi Hukum, 2022)
The factual conditions and determining factors for the fulfillment of the right to primary and secondary education are a re-actualization of state sovereignty. State sovereignty is the result of a reflection, abstraction and contemplation of a country's ability to maintain and maintain its existence in international law and relations. State sovereignty builds arguments about the laws and legal systems that apply in a country, including the fulfillment of the right to education in Indonesia. State sovereignty is a legal prescription to make, implement and enforce the law on people, objects and legal actions in the field of education in accordance with applicable standards and laws. Legal rights and obligations are formed and interact with each other in the legal system of a country so that the factual conditions and determining factors for the right to primary and secondary education in border areas are the sovereignty of the Indonesian state itself in accordance with the international agenda accepted by Indonesia in the field of education. The concept of state sovereignty is one of the most important elements in determining rights and obligations in international law. State sovereignty in international law establishes a standard identity of subjects of international law. State sovereignty is a legal prescription to make, implement and enforce the law on people, objects and legal actions. The prescription creates an agreement between the right holder and the right holder. The truth and fulfillment of the law becomes the standardization of state behavior towards its citizens or individual groups within the country within the framework of the protection, fulfillment and promotion of human rights in its territory or jurisdiction, including the right to basic and secondary education in the border areas of the Indonesian state.